2022
DOI: 10.1109/access.2022.3167699
|View full text |Cite
|
Sign up to set email alerts
|

Amaretto: An Active Learning Framework for Money Laundering Detection

Abstract: Monitoring financial transactions is a critical Anti-Money Laundering (AML) obligation for financial institutions. In recent years, machine learning-based transaction monitoring systems have successfully complemented traditional rule-based systems to reduce the high number of false positives and the effort needed to review all the alerts manually. Unfortunately, machine learning-based solutions also have disadvantages: while unsupervised models can detect novel fraudulent patterns, they are usually characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Luo et al [27] demonstrated the effectiveness of using a GRU to extract deep temporal features from information flows, contributing to the exploration of dynamic temporal dataset features. Labanca D et al [28] proposed using a GRU to automatically extract implicit temporal features from bank transaction data and built a fusion model with features extracted using self-attention mechanisms as an alternative to traditional rulebased methods. Additionally, several works have proposed using transformer models [39], which were originally designed for processing language sequences and have achieved good results.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Luo et al [27] demonstrated the effectiveness of using a GRU to extract deep temporal features from information flows, contributing to the exploration of dynamic temporal dataset features. Labanca D et al [28] proposed using a GRU to automatically extract implicit temporal features from bank transaction data and built a fusion model with features extracted using self-attention mechanisms as an alternative to traditional rulebased methods. Additionally, several works have proposed using transformer models [39], which were originally designed for processing language sequences and have achieved good results.…”
Section: Related Workmentioning
confidence: 99%
“…They address the vanishing and exploding gradient issues faced by traditional RNNs by introducing gate mechanisms that capture long-term dependencies. Furthermore, a GCN [28] is a deep learning model for processing graph data that captures the relationships between nodes by performing convolution operations on the input graph structure. GCN-GRU and MGC-LSTM [33] are fusion models that execute graph convolution operations on a static graph constructed from the entire training set in combination with GRUs and LSTM networks, respectively.…”
Section: Baselinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective AML systems are necessary for organizations to reduce the risk of financial losses from money laundering. AML involves identifying suspicious activities through customer transaction analysis using software, databases, and analytical tools (Labanca et al, 2022). Cryptocurrencies and blockchain technology present challenges in implementing traditional AML practices due to their decentralized and transparent nature.…”
Section: Anti-money Launderingmentioning
confidence: 99%
“…Training high-performance supervised classifiers for FD is crucial, but the lack of labeled data makes it challenging to train such ML models (Labanca et al, 2022). The process of labeling an entire dataset requires a vast sample of manually reviewed transactions, which is often unpractical due to the high costs involved and the limited investigative time and budget available for companies (Barata et al, 2021).…”
Section: Introductionmentioning
confidence: 99%